2022
DOI: 10.1029/2022gl098093
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Vertical Shear Leads to Earlier Secondary Eyewall Formation in Idealized Numerical Simulations

Abstract: Idealized numerical experiments show that stronger shear is more favorable for tropical cyclone secondary eyewall formation (SEF) than weaker shear amid a moist‐tropical environment when the shear magnitude is smaller than 15 m s−1. In particular, the larger the shear, the earlier the SEF occurs. A stationary banding complex (SBC) prevails before SEF in the large shear experiments, suggesting that SBCs are helpful in the SEF. Furthermore, a well‐organized stratiform sector is associated with the SBC. With incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…(2023), X. H. Liu et al. (2022), and Miller and Zhang (2019). Since the warm core in SHE72_AXI was centered at about 15–16 km height, we chose 16 and 13 km as examples to show how the warm‐core particles were transported outward and the surrounding particles were transported inward during the early TC weakening (Figures 4a, 4b, 4e, and 4f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2023), X. H. Liu et al. (2022), and Miller and Zhang (2019). Since the warm core in SHE72_AXI was centered at about 15–16 km height, we chose 16 and 13 km as examples to show how the warm‐core particles were transported outward and the surrounding particles were transported inward during the early TC weakening (Figures 4a, 4b, 4e, and 4f).…”
Section: Resultsmentioning
confidence: 99%
“…To understand how the high θ air within the upper-level warm core is transported outward, leading to the weakening of the warm core, we tracked the air particles using an advection correction trajectory algorithm following Dai et al (2023), X. H. Liu et al (2022), andMiller and. Since the warm core in SHE72_AXI was centered at about 15-16 km height, we chose 16 and 13 km as examples to show how the warmcore particles were transported outward and the surrounding particles were transported inward during the early TC weakening (Figures 4a,4b,4e,and 4f).…”
Section: Figures 1a and 1bmentioning
confidence: 99%
“…Many studies have focused on the onset of SEF and proposed plenty of physical processes and dynamics to explain SEF (e.g., Fang & Zhang, 2012; Huang et al., 2012; Montgomery & Kallenbach, 1997; Rozoff et al., 2006; Terwey & Montgomery, 2008). These studies hypothesized the origin of SEF from different aspects such as outward‐propagating vortex‐Rossby waves (e.g., Montgomery & Kallenbach, 1997), eddy‐mean‐flow processes (e.g., Rozoff et al., 2006, 2012; Terwey & Montgomery, 2008; Wang et al., 2016, 2019), boundary layer processes (e.g., Abarca & Montgomery, 2013; Huang et al., 2012; Kepert, 2013; Wu et al., 2012; Zhang et al., 2017), and asymmetric rainband processes (e.g., Dai et al., 2017; Didlake et al., 2018; Didlake & Houze, 2013; Fang & Zhang, 2012; Liu et al., 2022; Qiu & Tan, 2013; Wang & Tan, 2022; Yu & Didlake, 2019; Yu et al., 2021; Zhang et al., 2017). However, the prediction of SEF remains a challenge because the initiating mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the internal processes, environmental forcings can also influence SEF through rainband convection. It is reported that several environmental forcings may favor SEF by facilitating ORBs and their stratiform sectors (e.g., beta effect [Fang & Zhang, 2012]; westerly jet [Dai et al., 2017]; vertical wind shear [Liu et al., 2022; Y.‐F. Wang & Tan, 2022]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the internal processes, environmental forcings can also influence SEF through rainband convection. It is reported that several environmental forcings may favor SEF by facilitating ORBs and their stratiform sectors (e.g., beta effect ; westerly jet [Dai et al, 2017]; vertical wind shear [Liu et al, 2022;Y.-F. Wang & Tan, 2022]). Among all the environmental forcings, radiation also has profound influences on convection in TC (e.g., Ruppert & O'Neill, 2019;Trabing et al, 2019;Xu & Randall, 1995).…”
mentioning
confidence: 99%